2021
DOI: 10.1038/s42003-021-02077-2
|View full text |Cite
|
Sign up to set email alerts
|

Teasing apart the cell death pathways in HIV pathogenesis

Abstract: The progressive loss of CD4 + T cells has been recognised as being central to HIV-1 pathogenesis, however a precise understanding of the underlying mechanisms and, consequently, improved therapies have yet to be achieved. Zhang et al. have recently shown in HIV-1 patients that the NLRP3 inflammasome pathway, which plays a key role in innate immunity, is a crucial mediator of the loss of CD4 + T cells. This advance could inform the development of innovative anti-HIV-1 therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…On the one hand, NLRP3 inflammasome enhance the body's ability to clear the virus at the initial stage of HIV-1 infection as described by Reis et al (2019). On the other hand, NLRP3 inflammasome promotes pyroptosis of "bystander" CD4 + T cells (Montague-Cardoso, 2021;Zhang C. et al, 2021) and causes brain disease and neuroinflammation that are closely associated with NLRP3 inflammasome activation in microglia (Walsh et al, 2014;He et al, 2020). Finally, surprisingly, Paoletti et al demonstrated that HIV-1 induces NLRP3 degradation through purinergic receptor (P2Y2) signaling pathway, suggesting that HIV-1 has evolved an NLRP3-mediated immune escape strategy (Paoletti et al, 2019).…”
Section: Human Immunodeficiency Virus Type 1 and Inflammasomementioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, NLRP3 inflammasome enhance the body's ability to clear the virus at the initial stage of HIV-1 infection as described by Reis et al (2019). On the other hand, NLRP3 inflammasome promotes pyroptosis of "bystander" CD4 + T cells (Montague-Cardoso, 2021;Zhang C. et al, 2021) and causes brain disease and neuroinflammation that are closely associated with NLRP3 inflammasome activation in microglia (Walsh et al, 2014;He et al, 2020). Finally, surprisingly, Paoletti et al demonstrated that HIV-1 induces NLRP3 degradation through purinergic receptor (P2Y2) signaling pathway, suggesting that HIV-1 has evolved an NLRP3-mediated immune escape strategy (Paoletti et al, 2019).…”
Section: Human Immunodeficiency Virus Type 1 and Inflammasomementioning
confidence: 99%
“…(2019) . On the other hand, NLRP3 inflammasome promotes pyroptosis of “bystander” CD4 + T cells ( Montague-Cardoso, 2021 ; Zhang C. et al., 2021 ) and causes brain disease and neuroinflammation that are closely associated with NLRP3 inflammasome activation in microglia ( Walsh et al., 2014 ; He et al., 2020 ). Finally, surprisingly, Paoletti et al.…”
Section: Human Immunodeficiency Virus Type 1 and Inflammasomementioning
confidence: 99%